2022
DOI: 10.3390/ma15196749
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microstructure Refinement on the Corrosion Behavior of the Bioresorbable Mg-1Zn-0.2Ca and Mg-1Ca Alloys

Abstract: This paper presents a comprehensive study of the effect of the processing by high-pressure torsion (HPT) on the corrosion behavior in Ringer’s solution for two popular bioresorbable magnesium alloys—Mg-1Ca and Mg-1Zn-0.2Ca. Three states were studied for each alloy—the initial homogenized state, the as-HPT-processed state and the state after subsequent annealing at 250 and 300 °C. It is shown that HPT processing results in a very strong grain refinement in both alloys down to a mean grain size of about 210 nm f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The positive effect of grain refinement on the corrosion resistance of Mg alloys has already been reported in the literature [ 30 , 31 , 32 ] and related to more uniform distribution of surface defects such as dislocations and grain boundaries. In the case of the Mg-Sr system, an additional factor to increase the corrosion resistance in the deformed states can be attributed to the fragmentation and partial dissolution of the second phases due to SPD, which is consistent with the findings reported in [ 18 ].…”
Section: Resultsmentioning
confidence: 83%
“…The positive effect of grain refinement on the corrosion resistance of Mg alloys has already been reported in the literature [ 30 , 31 , 32 ] and related to more uniform distribution of surface defects such as dislocations and grain boundaries. In the case of the Mg-Sr system, an additional factor to increase the corrosion resistance in the deformed states can be attributed to the fragmentation and partial dissolution of the second phases due to SPD, which is consistent with the findings reported in [ 18 ].…”
Section: Resultsmentioning
confidence: 83%
“…It was concluded that HPT encourages the formation of special structures in Mg-1Zn-0.2Ca and Mg-1Ca alloys, thus decreasing the potential difference between the anode ( Mg 2 Ca) and the cathode ( α − Mg) by controlling the dispersion of eutectics region and avoiding the dissolution of large regions of the anode that cause surface pitting and corrosion propagation. Post-HPT annealing resulted in a conversion of [49].…”
Section: Magnesium and Magnesium Based Alloysmentioning
confidence: 99%
“…The design of the microstructure through alloying, heat treatment, and thermomechanical processing, on the one hand, and the protection of the surface using coatings and surface modification techniques, on the other, represent the two main approaches for enhancing the corrosion performance of biomedical Mg alloys. The optimization of the alloying content aims at controlling the number and composition of secondary phase particles or reducing the electrode potential difference between them and the Mg matrix [9][10][11][12][13][14][15] as well as selection of the optimal parameters of the heat treatments and thermomechanical processes, including extrusion, hot-rolling, equal channel angular pressing, and other severe plastic deformation techniques [16][17][18][19][20][21][22][23]. Various methods for protecting the Mg surface from corrosion, including conversion [24][25][26] and organic coatings [27,28], anodizing and plasma electrolytic oxidation [29,30], surface heat treatment, and plastic deformation [9,31,32], have been proposed so far.…”
Section: Introductionmentioning
confidence: 99%